Nail neoplasms. Issue 3 (March 2017) - Park, Ji‐Hye; Lee, Dong‐Youn; Kim, Noori
Abstract: Nail neoplasms include all tumors occurring in the nail or periungual apparatus tissue. While some nail tumors can be similar to tumors located on the skin, others are unique. Both benign and malignant lesions can affect the nail apparatus. In particular, early malignant tumors like melanoma and squamous cell carcinoma can present similarly to onychomycosis or benign melanonychia and frequently missed by clinicians. Therefore, physicians should be aware of nail structures and the characteristics of nail tumors. Our review covers the normal nail structure and the most common nail tumors from benign to malignant.